Adaptation and Validation of the Spanish Version of the Instrument to Evaluate Nurses’ Attitudes Toward Communication With the Patient for Nursing Students - María del Carmen Giménez-Espert (Frontiers Media S.A., 2021)
Communication is essential to the quality of care and patient satisfaction. It has been linked to positive patient outcomes, increased engagement, improved health outcomes, and safe practices. Given these benefits and the association between attitudes and behaviors, as behaviors can be predicted by studying attitudes, assessing attitudes of nursing students toward patient communication is critical for future nursing professionals. For this purpose, the main aim of this study was to adapt and validate an instrument to measure nurses’ attitudes toward communication (ACO) for nursing students. The ACO with patients was analyzed. Then, differences in the dimensions of the instrument (ACO) for nursing students according to an academic course and the correlations were calculated. A cross-sectional study was carried out in a convenience sample of 1,417 nursing students from five universities in the Valencian Community (Spain) during the 2018/2019 academic year and 83.8% (1,187) were women. The reliability was analyzed by using Cronbach’s alpha and composite reliability (CR). Analysis of construct validity was performed with exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). The instrument adapted from nurses to nursing students was composed of 25 items grouped in three dimensions: affective, cognitive, and behavioral. The psychometric properties suggested that the instrument ACO for nursing students was reliable and valid. The ACO of nursing students was positive with high levels in cognitive and behavioral dimensions, while scores were worst in the affective component. The second-year nursing students showed more positive attitudes in the affective dimension, while in the cognitive and behavioral dimensions, the most positive attitudes were found in the first year. In the correlations, the behavioral and cognitive dimensions showed a significant, positive, and very high correlation. These findings should be considered in developing academic plans to improve the effectiveness of the communication education process of the students to increase the quality of patient care and well-being of nursing students.